Rancang Bangun Mesin Uji Abrasi Material Alumunium Terhadap Pelumasan Oli - Eko Saputra, Aditiya Wahyu; Wulandari, Diah; Sakti, Arya Mahendra; Puspitasari, Dewi (Jurnal Rekayasa Mesin, 2026)
Abrasion is a common wear mechanism that occurs in machine components due to repeated frictional contact, particularly in aluminum materials that are widely used because of their light weight and corrosion resistance. Nevertheless, aluminum remains susceptible to wear when the lubrication system does not perform optimally. This study aims to design and develop a laboratory-scale abrasion testing machine and to analyze the effect of rotational speed on the wear behavior of aluminum 6061 under oil lubrication. The research employed a research and development method consisting of design, fabrication, assembly, functional testing, and abrasion testing stages. Abrasion tests were conducted at rotational speeds of 500, 1000, and 1500 RPM with a constant load of 3 kg, a test duration of 30 minutes, and Shell SAE 10W-30 oil as the lubricant. Quantitative data were obtained from the measurement of specimen mass loss before and after testing, while qualitative analysis focused on machine performance and operational stability during testing. The results indicate that the developed abrasion testing machine operated properly and was capable of producing consistent wear data. The mass loss of aluminum specimens increased with higher rotational speeds, with the highest average wear observed at 1500 RPM. This study contributes by providing a simple and cost-effective abrasion testing machine for laboratory applications and by offering insights into the influence of rotational speed on the wear behavior of aluminum under lubricated conditions.